Demonstrasi Plot Budidaya Melon secara Hidroponik dalam Screenhouse dengan Modifikasi Insulasi Panas pada Kelompok Tani Barokah di Kecamatan Pakal, Surabaya: Hydroponic Melon Cultivation Demonstration in an Insulated Screenhouse at Barokah Farmer Group, Pakal District, Surabaya - Sasongko, Purnomo Edi; Chakim, M. Ghufron; Handini, Aline Sisi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Urban farming activities in Surabaya have continued to grow rapidly since the end of the COVID-19 pandemic in 2022, meeting approximately 20 percent of the city's vegetable needs. The improved skills of various vegetable cultivation groups, including the Barokah Farmers Group in Babat Jerawat Village, Pakal District, have led them to be named "Jawara". Armed with this achievement, they are attempting to expand into seasonal fruit farming using hydroponic technology under the shade of a screen house. On the other hand, Surabaya's hot weather and relatively high humidity are obstacles to implementing hydroponic cultivation systems in screenhouses. Exposure to intense sunlight during the day can increase the temperature of the pipes containing the net pots and nutrient reservoirs to 45°C, thus impacting the temperature of the AB Mix nutrient solution and the physiology of melon plant roots. Armed with experience from research and melon cultivation practices, the community service implementation team conducted a demonstration plot of superior hydroponic melon cultivation in a screenhouse. Based on the findings of the hydroponic installation research on campus, several modifications have been made to the hydroponic installation, including the addition of a cooling layer for the netpots and hydroponic nutrient reservoirs. The added heat insulation layer maintains the temperature of the piping and nutrient reservoir between 30-32°C. This is expected to allow the melon plants to grow normally without environmental stress until harvest, when they yield optimal fruit.